2013
DOI: 10.1590/s0104-40602013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Formação de professores em instituições públicas de ensino superior no Brasil: diversidade de problemas, impasses, dilemas e pontos de tensão

Abstract: Este artigo apresenta problemas, impasses, dilemas e pontos de tensão atuais na formação de professores para a Educação Básica em instituições públicas brasileiras. Os dados da pesquisa documental exploratória advêm de levantamento de teses registradas no Banco de Teses da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (Capes) e artigos publicados no site da Scientific Eletronic Library Online (SciELO)/Brasil. Foi realizado levantamento de trabalhos publicados no período de 2006 a 2013. Encontramo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
4
0
5
Order By: Relevance
“…Gatti (2009Gatti ( , 2010 highlighted, as was mentioned, the curricular fragility of Pedagogy Graduate Courses. Mindal and Guérios (2013) report how few are the researches that deal specifically with the process of teacher training, while Guérios, Cyrino, Vieira e Melo (2016) identify the same regarding the teacher who teaches mathematics as a focus of study in the Southern Region of Brazil.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Gatti (2009Gatti ( , 2010 highlighted, as was mentioned, the curricular fragility of Pedagogy Graduate Courses. Mindal and Guérios (2013) report how few are the researches that deal specifically with the process of teacher training, while Guérios, Cyrino, Vieira e Melo (2016) identify the same regarding the teacher who teaches mathematics as a focus of study in the Southern Region of Brazil.…”
Section: Final Remarksmentioning
confidence: 99%
“…By the time that Gatti was the research coordinator at the Carlos Chagas Foundation, she gave an interview to Época Magazine and stated in its November 14, 2016 headline that "One of the major Education researchers in Brazil says that most of the mind sets in Pedagogy Graduate Courses is anachronistic and does not meet the social demands of the country". Mindal and Guérios (2013) identified that few researches in the Brazilian scenario focus on teachers themselves and on the specificity of their education. In the mapping these two authors carried out in the CAPES' theses database and in the papers published on the SciELO/Brazil website from 2006 to 2013, they found 2,550 works when using the key words "teacher training".…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps, considering this perspective as a component of the complexity of the educational field (Mindal & Guérios, 2013), it is possible to minimize the recurrence of problems that generate conflicts in the formation of teachers in Brazilian education.…”
Section: The Development Of Creativity At Schoolmentioning
confidence: 99%
“…Tal afirmação, a do estatismo, advém do que pesquisas evidenciam em seus resultados acerca da recorrência de problemas e frágeis resultados, apesar das tentativas institucionais para vencê-los ou, ao menos, minorálos. Argumentarei sobre essa afirmação por meio das produções de Gatti (2013Gatti ( , 2014, Gatti et al (2019), Mindal e Guérios (2013) e Guérios e Gonçalves (2019).…”
Section: Introductionunclassified